Evaluation of Nasolabial Aesthetics and Self-Image Satisfaction among 16- to 20-Year-Old Patients with Cleft Lip and Palate in Northeast Thailand - Surakunprapha, Palakorn; Pradubwong, Suteera; Jenwitheesuk, Kamonwan; Pisek, Poonsak; Chowchuen, Bowornsilp (Archives of Plastic Surgery, 2024)
Background Cleft lip and palate (CLP) impact nasolabial appearance, influencing the physical, psychological, and quality of life (QoL) of affected individuals. Evaluations of the nasolabial aesthetics by patients and medical professionals (both experienced and inexperienced) are critical for enhancing patient care.Methods This cross-sectional study enrolled 32 patients aged 16 to 20 years with CLP who underwent continuous treatment at a university hospital in Thailand. Participants were asked to complete the Thaicleft QoL questionnaire for nasolabial aesthetic self-assessment and had their two-dimensional facial images captured and then evaluated by two groups of medical evaluators: four experienced and four inexperienced professionals. Data are presented as means and percentages, with analysis including standard deviations, Cronbach's α for evaluator consistency, kappa for interrater reliability, and the Wilcoxon signed-rank test to compare aesthetic judgments between the experienced and inexperienced medical evaluators.Results Among the 32 patients, 19 (59.37%) were females, and 22 (68.75%) had unilateral CLP and 10 (31.25%) had bilateral CLP, all reporting high nasolabial aesthetic satisfaction. Inexperienced evaluators assigned higher aesthetic scores than their experienced counterparts (p = 0.01), with statistically significant agreement among inexperienced evaluators in their assessments (p < 0.05). Both group of evaluators demonstrated high reliability in terms of the lip.Conclusion Experienced evaluators assigned lower aesthetic scores than inexperienced evaluators did. The patients themselves expressed high levels of satisfaction with their nasolabial appearance, indicating that the treatment outcomes were favorable from the patients' perspective.
Keywords: evaluation; nasolabial appearance; cleft lip and palate; Thailand